Modified dispersive solid‐phase extraction and cleanup followed by GC‐MS/MS analysis to quantify ultraviolet filters and synthetic musk compounds in soil samples. Issue 16 (22nd June 2021) - Ramos, Sara; Homem, Vera; Santos, Lúcia
Abstract: A simple method for the analysis of 13 synthetic musk compounds and six ultraviolet filters in soil samples was developed using a modified dispersive solid‐phase methodology known as "Quick, Easy, Cheap, Effective, Rugged and Safe, " followed by gas chromatography–triple quadrupole mass spectrometry. The methodology was validated by assessing linearity ranges, detection limits, precision, and accuracy. The method detection limit ranged between 0.01 and 10.00 ng/g dry weight and accuracy from 81 to 122%. A good precision was achieved, with relative standard deviation <10%. The applicability of the methodology was tested using different types of soils. Both synthetic musks and ultraviolet filters were detected in all soil samples. The most frequently detected compounds were benzophenone, octocrylene, 2‐ethylhexyl 4‐dimethylaminobenzoate, 2‐ethylhexyl 4–methoxycinnamate, and galaxolide. Higher levels were detected for benzophenone (maximum value of 158 ng/g dry weight) and octocrylene (137 ng/g dry weight). In comparison with conventional techniques, this method uses lower amounts of solvents and sorbents, producing less waste ("greener" technique) and comparable performances. In addition, it presents as main advantages the simplicity, speed (short extraction/cleaning time), low cost, and minimum handling of extracts, which can minimize the possibility of samples cross‐contamination.